Character association and identification of trait specific introgression in restorer lines of sunflower (Helianthus annuus L.) - Girish1, Vikas V. Kulkarni2*, B. V. Tembhurne3, J. R. Diwan3 and Sreedevi S. Chavan2 (Electronic Journal of Plant Breeding, 2022)
The study was carried out involving 40 MAGIC crosses of sunflower restorer lines along with 10 parental checks during rabi, 2020 grown in augmented block design with four blocks at MARS, UAS Raichur with an objective of assessing variation and character association for yield attributing traits. The highest estimates of GCV, PCV, heritability and genetic advance as per cent of mean were recorded for seed yield per plant followed by 100-seed weight. Seed yield per plant recorded a highly significant positive association with plant height and head diameter. Path analysis studies indicated plant height had the highest positive direct effect on seed yield per plant followed by oil content. Trait specific introgression studies revealed that R-127-1 × RⅡ, CSFI-99 × RⅢ and No-30 × RⅣ showed the highest percentage (87.5%) of introgression with the expression of seven out of eight traits.